2016
DOI: 10.1016/j.ajme.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Species identification and antifungal susceptibility pattern ofCandidaisolates in cases of vulvovaginal candidiasis

Abstract: Vulvovaginal candidiasis (VVC) remains one of the most common infections of the female genital tract. Correct identification of the isolated Candida species is essential to direct the empirical antifungal therapy. Objectives: This local study was conducted to identify the spectrum of Candida species associated with VVC using different phenotypic and genotypic methods and assess their antifungal susceptibility pattern. Materials and methods: High vaginal swabs were collected from 125 patients presenting with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
34
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 68 publications
12
34
3
3
Order By: Relevance
“…Elfeky et al [31], using disk diffusion method, demonstrated that 10.5% of C. albicans isolates were resistant to FLZ and VRZ, but 100% of the isolates were susceptible to AMB. Fothergill et al [25] revealed that FLZ resistance was increased in C. albicans from 2.1% to 5.7% and that VRZ resistance was 4.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Elfeky et al [31], using disk diffusion method, demonstrated that 10.5% of C. albicans isolates were resistant to FLZ and VRZ, but 100% of the isolates were susceptible to AMB. Fothergill et al [25] revealed that FLZ resistance was increased in C. albicans from 2.1% to 5.7% and that VRZ resistance was 4.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Zone of inhibition around the disc was measured after incubating the media at 37 °C for 24 h. In case of C. krusei , repeated antifungal susceptibility testing to fluconazole was performed [12, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…This result shows that some phenotypic tools are still useful to the correct diagnosis of VVC, with the advantage of being of the most accurate method for the identification of Candida species, whereas molecular tools could confirm Candida species identification (Table ) (ElFeky et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; ElFeky et al . ). Thus, many professionals recommend in vitro susceptibility tests in cases of difficult treatment or infections caused by less frequent species to which there is less information (Mendling et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation